Value Education in the Digital Era: Its Impact on the Emotional Intelligence of Elementary School Students - Muhammad Alfi Syahrin; Rifqi Khoiril Anam; Rani Asmara; Dody Tisna Amijaya (AL IBTIDAIYAH: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This study aims to analyze the role of value education in developing the emotional intelligence of elementary school students in the digital era. The study employed a qualitative approach using an intrinsic case study design conducted in several elementary schools and Islamic elementary schools in urban Probolinggo, Indonesia. The participants consisted of 30 students aged 8–12 years, 10 teachers, and 15 parents selected through purposive sampling. Data were collected through in-depth interviews, participant observation, and document analysis, and were analyzed using descriptive qualitative analysis through data reduction, data display, and conclusion drawing. The findings reveal that value education contributes significantly to strengthening students’ emotional regulation, empathy, prosocial behavior, and social responsibility. Value internalization occurred effectively through contextual learning, social habituation, reflective interaction, and teacher role modeling in everyday school life. The study also found that the synergy between schools and families reinforced value internalization and children’s emotional intelligence development. Furthermore, digital technology demonstrated an ambivalent role; it could support emotional development through educational media and social communication, yet it also had the potential to increase distraction, impulsivity, and emotional instability when not accompanied by adequate value-based guidance. This study confirms that value education in the digital era should be positioned as a holistic socio-emotional formation process integrated with digital literacy, family involvement, and reflective learning practices in elementary education.